HUBUNGAN PENGETAHUAN DAN PERSONAL HYGIENE DENGAN KEJADIAN SCABIES PADA SANTRI PONDOK PESANTREN DARUL MUKHLISIN KABUPATEN ACEH TENGAH - Zahara, Ade; Haryono, Iswahyudi; Zulfikar (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Scabies is a contagious skin disease caused by the infestation of the mite Sarcoptes scabiei, which frequently occurs in crowded environments such as Islamic boarding schools. This study aims to determine the relationship between knowledge and personal hygiene with the incidence of scabies among students at the Darul Mukhlisin Islamic Boarding School in Aceh Tengah District. The research method used is quantitative analysis with a cross-sectional approach. The research population consisted of all male students from the MTs (Islamic Junior High School) of Darul Mukhlisin Islamic Boarding School, totaling 160 students. The sample consisted of 62 students selected through random sampling. Data were collected through structured questionnaires and field observations and analyzed using the chi-square test with a 95% significance level. The results of the study showed that the chi-square significance value for knowledge was (p-value=0.000) <0.05 and for personal hygiene was (p-value=0.002) <0.05. This indicates a significant relationship between knowledge and personal hygiene with the incidence of scabies in the boarding school. Based on the research findings, it is concluded that students with good knowledge and good personal hygiene practices have a lower risk of experiencing scabies. Therefore, it is recommended that students improve personal hygiene, and boarding school management strengthen health education. Keywords : Scabies, Personal Hygiene, Islamic Boarding School, Students